Muscle‐strain injury exudate favors acute tissue healing and prolonged connective tissue formation in humans. Issue 9 (18th June 2019) - Bayer, Monika L.; Bang, Louise; Hoegberget‐Kalisz, Maren; Svensson, Rene B.; Olesen, Jens L.; Karlsson, Mads M.; Schjerling, Peter; Hellsten, Ylva; Hoier, Birgitte; Peter Magnusson, S.; Kjaer, Michael
ABSTRACT: Traumatic strain injury in skeletal muscle is often associated with fluid accumulation at the site of rupture, but the role of this injury exudate (EX) in cellular responses and healing is unknown. We aimed to characterize the EX sampled from human hamstring or calf muscles following a strain injury ( n = 12). The cytokine and growth‐factor profile, gene expression, and transcriptome analysis of EX‐derived cells were compared with blood taken simultaneously from the same individuals. Cellular responses to the EX were tested in 3‐dimensional (3D) culture based on primary human fibroblasts and myoblasts isolated from hamstring muscles. The EX contained a highly proinflammatory profile with a substantial expression of angiogenic factors. The proinflammatory profile was present in samples taken early postinjury and in samples aspirated several weeks postinjury, suggesting persistent inflammation. Cells derived from the EX demonstrated an increased expression of fibrogenic, adipogenic, and angiogenesis‐related genes in comparison with blood cells. The injury EX stimulated fibroblast proliferation 2‐fold compared with plasma, whereas such an effect was not seen for myoblasts. Finally, in 3D cell culture, the EX induced an up‐regulation of connective tissue‐related genes. In summary, EX formation following a muscle‐strain injury stimulates fibroblast proliferation and the synthesis of connective tissue in fibroblasts. This suggests that the EX promotes an acute tissue‐healing response but potentially also contributes to the formation of fibrotic tissue in the later phases of tissue repair.—Bayer, M. L., Bang, L., Hoegberget‐Kalisz, M., Svensson, R. B., Olesen, J. L., Karlsson, M. M., Schjerling, P., Hellsten, Y., Hoier, B., Magnusson, S. P., Kjaer, M. Muscle‐strain injury exudate favors acute tissue healing and prolonged connective tissue formation in humans. FASEB J. 33, 10369–10382 (2019). www.fasebj.org